Stiffness and surface topology of silicone implants competitively mediate inflammatory responses of macrophages and foreign body response - Sicen He; Qingrong Zhang; Jiezhi Jia; Wei Xia; Shengnan Chen; Fanyi Min; Yanlin Song; Yunlong Yu; Jiangfeng Li; Zheng Li; Gaoxing Luo (Materials Today Bio)
Adverse inflammatory responses, dominated by macrophages, that are induced by physical cues of silicone implants can heavily damage the life quality of patients via causing fibrosis and device failure. As stiffness and surface topology affect macrophages at the same time, the competition or partnership among physical cues against the regulation of macrophages is still ambiguous. Herein, a series of PDMS implants with different stiffness at ∼ MPa and surface topology at tens of micrometers were fabricated to investigate the relationship, the regulation rule, and the underlying mechanism of the two physical cues against the inflammatory responses of M1 macrophages. There is a competitive rule: surface topology could suppress the inflammatory responses of M1 macrophages in the soft group but did not have the same effect in the stiff group. Without surface topology, lower stiffness unexpectedly evoked stronger inflammatory responses of M1 macrophages. Implanting experiments also proved that the competitive state against mediating in vivo immune responses and the unexpected inflammatory responses. The reason is that stiffness could strongly up-regulate focal adhesion and activate the MAPK/NF-κB signaling axis to evoke inflammatory responses, which could shield the effect of surface topology. Therefore, for patient healthcare, it is crucial to prioritize stiffness while not surface topology at MPa levels to minimize adverse reactions.